Роль белков нервной регуляции PGP 9,5 и NGF в механизме туберкулёзного воспаления - Zubareva, T. S.; Lykova, K. O.; Leontieva, D. O.; Krylova, Yu. S.; Dokhov, M. A. (Патогенез, 2022)
Тезисы конференции